2013
DOI: 10.1039/c3an36838f
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between dissolution, gas oversaturation and outgassing of solutions determined by Broadband Acoustic Resonance Dissolution Spectroscopy (BARDS)

Abstract: The addition of a solute to a solvent is known to reduce the solubility of dissolved gases in solution which leads to gas oversaturation and outgassing of the solvent. The importance of the processes involved have received relatively little attention due to a limited capacity to elucidate their effects in real time. Broadband Acoustic Resonance Dissolution Spectroscopy (BARDS) is a recently introduced acoustic approach which can monitor changes in the compressibility of a solvent due to outgassing. BARDS spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…All experiments were performed in duplicate, and average readings with error bars representing the data spread are presented. The time courses of the observed acoustic profiles were highly reproducible under standardized conditions of constant volume, mass, temperature, and stirring rate (12). In general, the dissolution process is complete at the frequency minimum.…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…All experiments were performed in duplicate, and average readings with error bars representing the data spread are presented. The time courses of the observed acoustic profiles were highly reproducible under standardized conditions of constant volume, mass, temperature, and stirring rate (12). In general, the dissolution process is complete at the frequency minimum.…”
Section: Methodsmentioning
confidence: 85%
“…A custom prototype spectrometer was built and used to investigate the BARDS responses (12,13). It consists of a chamber with a glass dissolution vessel, a microphone (Sony ECM-CS10, range 100-16 kHz), a magnetic stirrer, and a stir bar.…”
Section: Instrumentationmentioning
confidence: 99%
“…Results from BARDS analysis indicated that water transfer into MPC powder particles became inhibited as the protein content of the MPC powders increased (Figures 2, 3, Table 1). For example, rehydration of MPC35 yielded a minimal BARDS response and a rapid return to steady-state (<400 s), while the time (60 min) required to reach steady-state for MPC90 (0.2%) (Figure 2) is unprecedented in its length compared to previous BARDS studies (Fitzpatrick et al, 2012a(Fitzpatrick et al, , 2012b(Fitzpatrick et al, , 2013(Fitzpatrick et al, , 2014. Release of gas from powders can be used to indirectly investigate water transfer in dairy powders (Richard et al, 2012;Hauser and Amamcharla, 2016;).…”
Section: Discussionmentioning
confidence: 95%
“…The pitch of the resonance modes in the solution change significantly when the powder is added 10 min. Otherwise, remaining gas oversaturation may lead to an over-response (Fitzpatrick et al 2013).…”
Section: Experimental Procedures For Bards Experimentsmentioning
confidence: 99%
“…A custom prototype spectrometer was built and used to investigate the BARDS responses. 8,9 It consists of a chamber with a glass tumbler, microphone (Sony ECM-CS10, range 100 Hz to 16 kHz), a magnetic stirrer and follower. There is access at the front for the dissolution vessel and at the top in order to place a sample in a weighing boat on a tipper motor for introduction of the solute.…”
Section: Instrumentationmentioning
confidence: 99%